Cognitive recovery after severe traumatic brain injury in children/adolescents and adults: Similar positive outcome but different underlying pathways?. (June 2014) - Tavano, Alessandro; Galbiati, Susanna; Recla, Monica; Bardoni, Alessandra; Dominici, Chiara; Pastore, Valentina; Strazzer, Sandra
Abstract Primary objective: Does younger age at the time of severe traumatic brain injury (STBI) protect from cognitive symptoms? To answer this question, the authors compared the neuropsychological profile of late school-age children/adolescents and young adult patients at mid- and long-term recovery periods (6 and 12 months post-STBI). Methods and procedures: Twenty-eight children/adolescents and 26 clinically matched adults were tested on measures of general intelligence, attention, executive functions, visuoperceptual, visuospatial and visuoconstructive abilities. Coma duration and the post-acute Glasgow Outcome Scale (GOS) score were used as predictor variables in a series of regression analyses. Main outcomes and results: Children/adolescents and adults similarly improved on most measures, except for visuospatial and visuoconstructive skills, which worsened in time for children/adolescents. Coma duration significantly predicted performance IQ and visuoperceptual scores in children/adolescents. The GOS score significantly predicted performance and verbal IQ, sustained attention, visuoconstructive and long-term memory skills. Coma duration predicted executive function skills in both age groups. Conclusions: (1) No evidence was found for a neuroprotective effect of younger age at STBI; and (2) Coma duration and GOS score predicted neuropsychological recovery in children/adolescents and adults, respectively. This suggests the existence of underlying age-specific recovery processes after STBI.